Integrating Islamic Laws into Indonesian Data Protection Laws: An Analysis of Regulatory Landscape and Ethical Considerations - Tegar Islami Putra; Akbar Jihadul Islam; Abdullah Mufti Abdul Rahman (Universitas Negeri Semarang, 2024)
This study explores the intersection of personal data protection laws in Indonesia with Islamic principles, focusing on the regulatory landscape and ethical considerations surrounding data privacy. With the proliferation of digital technologies and data-driven processes, safeguarding personal information has become paramount. Drawing from legal frameworks, Islamic jurisprudence, and contemporary discussions on data privacy, this research investigates how Islamic principles inform and complement existing data protection measures in Indonesia. The analysis begins by examining the legal foundation of personal data protection in Indonesia, emphasizing key provisions of relevant legislation and constitutional mandates. It then delves into Islamic principles related to privacy, confidentiality, and ethical conduct, as derived from primary Islamic sources such as the Quran, Hadiths, and scholarly interpretations. The study evaluates the alignment between personal data protection laws and Islamic ethics, identifying areas of convergence and potential divergence. It explores the implications of Islamic principles for data handling practices, consent requirements, and accountability mechanisms within the Indonesian context. Furthermore, the research discusses the practical implications of integrating Islamic principles into data protection frameworks, considering challenges, opportunities, and best practices for ensuring compliance and ethical data governance. By bridging legal and ethical perspectives, this study contributes to a deeper understanding of personal data protection in Indonesia and offers insights into the role of Islamic principles in shaping contemporary approaches to privacy and confidentiality in the digital age. It underscores the importance of holistic and culturally approaches to data governance that respect both legal requirements and ethical norms derived from Islamic teachings.